ANALISIS TRANSPARANSI DAN AKUNTABILITAS PENGELOLAAN KEUANGAN DESA SEBAGAI SARANA GOOD GOVERNANCE (Studi Pada Pemerintahan Desa Putat Lor Dan Desa Putat Kidul Kecamatan Gondanglegi Kabupaten Malang Tahun 2016) - Lilis Sufiana; Nur Diana (e_Jurnal Ilmiah Riset Akuntansi, 2018)
ABSTRACTThe purpose of this research is to know whether the management ofvillage finances at the village of Putat Lor and Putat Kidul done transparentlyand accountably through the process:planning and budgeting,implementation,administration, reporting and responsibility. The descriptivewhich is done buy using the quantitative approach is used as the researchmethod. The data collection technique has been done by conductinginterview,observation, and dokumentation. While the data analysis has beendone by data reduction, presentation of data, conclucions and verification. Theresult of the research shows that generally the goverment at the Putat Lor andPutat Kidul village has been implemented the good goverment principle that istransparency and accountibility in managing village finances related to villagebudget (APBDesa) in 2016, even though not perfect yet. For example in theevaluation in only done at district but in the village has not implemented byinvolving all stakeholders. Therefore, sustainable improvement needs to bedone by the goverment at the Putat Lor and Putat Kidul Village to create aprosperous society.Keyword: transparency and accountibility, management of village finances,good governance.